Persuasion of War Documentary Films and Communication Technology Impact on Northeast Chinese Audience’s Behavior - Xiao, Wang; Nualnetr, Assis.Prof.Dr.Prapas (Journal of Dhamma for Life, 2025)
This article aimed to explore the communication value of war documentary films, the key factors affecting audience behavior, the impact of communication technology, and the role of war documentary films in enhancing ethnic community awareness. War documentary films are a witness to history and a carrier of national memory. Through in-depth exploration of historical events and characters, they guide the audience to think about social and historical issues, and stimulate national consciousness and patriotism. With the booming development of China's film and television industry, war documentary films should become an important way to influence Chinese audiences. However, with the explosive growth of internet information, the quality of war documentary films varies. This study uses a combination of qualitative and quantitative methods. Through in-depth interviews with 8 film directors, producers and audience members, and a questionnaire survey with 400 audience members in Northeast China as an overall sample, the study aims to understand the communication value of war documentary films, the key factors affecting audience behavior, the impact of communication technology, and the role of war documentary films in enhancing ethnic community awareness. The research results show that most audiences believe that the dissemination of war documentary films in China has important value, which can guide audiences to understand and remember history, trigger deep thinking, stimulate patriotic emotions, and strengthen the sense of national community. To play the role of war documentary films, it is necessary to base on history, culture and authenticity, and reasonably apply persuasion and communication techniques. At the same time, it is necessary to strengthen supervision and policy support to promote the production and dissemination of war documentary films.